Control interno al inventario de materiales y productos químicos y su incidencia en la rentabilidad de la hacienda Nayda, parroquia El Vergel, cantón Valencia, año 2013” previo a la obtención del título de ingeniera en contabilidad y auditoría c.p.a. - Garay Villacis, Mónica Katherine (2015)
Research conducted at the hacienda NAYDA is caused by the need to assess the Internal Control to the inventory of materials and chemical products in the area of Winery and its impact on profitability in the year 2013; for this purpose the approach of the objectives was the following: assess Internal Control and registration of inventory, analyze the compliance, estimate the effect on profitability and introduce the Internal Control report. Methods of analysis - synthesis and inductive - deductive responded to the risks detected in the study, in regards to the type of investigation was part of the field and documentary allowing the review of existing regulations to estimate compliance in the inventory record through substantive evidence and documents which revealed the weaknesses of the winery area. The design and implementation of Internal Control questionnaires is framed in the COSO I and due process. The results include that to refer to the existence of a responsible delivery of materials for field staff, 100% expressed that the winemaker is done. In relation to the inherent risk is set at 59%, the risk of detection by 15% and the overall risk of audit in 2.60%. The risk of control Hacienda NAYDA is the 29.38% and the level of confidence in 70.62% established as moderate. Internal Control report is made based on the results and findings that discourage the organizational development of the organization. Ending with the conclusions and recommendations of the project detailing the breach in IAS 2 in relation to the registration, management, custody and maintenance of the inventory of materials and chemicals and the correct use of the information in the area of warehouse of the company.